Lower and upper plate controls on crustal seismicity in the southern Central and Patagonian Andes - Correa Otto, Sebastian Ariel; Gianni, Guido Martin (Tectonics)
We analyze crustal seismological records to assess the origin of the variable seismic activity along the southern Central and Patagonian Andes (30°–55°S), an area associated with latitudinal changes in the lower-plate geometry, upper-plate deformation, and topography. We carried out a statistical analysis of the seismicity records at crustal depths of 0–50 km from an updated earthquake catalog. Studying the seismicity by its area covered, depth, latitude, and time, this analysis reveals a consistent and drastic decrease in the number of earthquakes south of 38.5°S. We note that the low seismicity area is spatially correlated with a thin, hot, and weak (at least in the forearc region) upper plate and the subduction of a young/warm lower plate with short slab depths (∼150–400 km) beneath Patagonia. Notably, the reduced upper plate seismicity is mimicked at depth by a similar decrease in lower plate seismicity associated with the presence of relatively shallow slabs south of 38.5°S. This observation allows us to suspect a genetic connection between lower plate properties and the striking reduction in the upper-plate seismicity. We tentatively suggest that the young/warm and short Nazca and Antarctic subducting plates, left after Neogene slab detachments, modified the thermomechanical upper plate structure, triggering the drastic decrease in crustal earthquakes. This process was likely aided by an inherited thin continental margin. This study reveals that slab detachment in non-collisional settings can impact upper-plate seismicity. Fil: Correa Otto, Sebastian Ariel. Universidad Nacional de San Juan. Facultad de Ciencias Exactas, Físicas y Naturales. Instituto Geofísico Sismológico Volponi; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - San Juan; Argentina Fil: Gianni, Guido Martin. Universidad Nacional de San Juan. Facultad de Ciencias Exactas, Físicas y Naturales. Instituto Geofísico Sismológico Volponi; Argentina. Consejo Nacional de ...